Advanced Biomedical Applications of Reactive Oxygen Species-Based Nanomaterials in Lung Cancer - Zhao, Nan; Xin, Hua; Zhang, Lening (Frontiers in Chemistry, 2021)
Over the years, lung cancer remains the leading cause of cancer deaths in worldwide. In view of this, increasingly importance has been attached to the further optimization and improvement of its treatment. Reactive oxygen species (ROS) play a key role in regulating tumor development and anti-cancer treatment. Recently, the development of nanomaterials provides new platforms for ROS-based cancer treatment methods, which can help to reduce side effects and enhance anti-cancer effects. In recent years, a variety of lung cancer treatment models have been reported, such as chemodynamic therapy (CDT), photodynamic therapy (PDT), radiation therapy (RT) and controlled drug release (CDR). In this review, we are going to discuss the possible mechanism of action and current research status of ROS-based nanomaterials in the treatment of lung cancer in order to provide constructive ideas for relative research and expect this work could inspire the future development of novel lung cancer treatments.